Fixation Locus in Patients with Bilateral Central Scotomas for Targets that Perceptually Fill In - Pratt, Joshua D. (Optom Vis Sci, 2014)
PURPOSE: In this experiment we investigated whether target type affects the retinal fixation location and stability in patients with bilateral central scotomas, and specifically whether targets expected to perceptually fill in are imaged at or near the vestigial fovea. METHODS: The retinal location and stability of fixation were measured using the Nidek MP-1 microperimeter in twelve patients with bilateral central scotomas for six types of fixation target, three expected to fill in and three that included letters. The approximate position of the vestigial fovea was delineated in 10 of the patients either by using residual retinal landmarks or by locating the residual foveal pit in a dense macular scan, obtained with a Spectralis Optical Coherence Tomographer. Fixation location and stability were compared for the different target types and referenced to the position of the vestigial fovea. RESULTS: All of the subjects except one fixated consistently on targets that included a letter using peripheral retinal locations outside of the central scotoma. Eleven of the twelve subjects used a retinal location closer to the vestigial fovea to fixate targets expected to fill in, compared to letters. Although four of the subjects imaged the fill-in targets at or within a half degree of the vestigial fovea, six other subjects imaged the fill-in targets at a retinal locus removed from the vestigial fovea. Target type produced no overall significant difference in fixation stability, specified in terms of bivariate contour ellipse area (BCEA). However, in some individual subjects, fixation tended to be more stable on letter targets than on fill-in targets. CONCLUSIONS: In patients with central field loss, letter targets generate more consistent fixation behavior than fill-in targets and should be used for eccentric viewing training and perimetry.